Contemporary engineering economics - Park, Chan S. (England Pearson Education Limited, 2016)
"Contemporary Engineering Economics teaches engineers how to make smart financial decisions in an effort to create economical products. As design and manufacturing become an integral part of engineers' work, they are required to make more and more decisions regarding money. The Sixth Edition helps students think like the 21st century engineer who is able to incorporate elements of science, engineering, design, and economics into his or her products. This text comprehensively integrates economic theory with principles of engineering, helping students build sound skills in financial project analysis"--Amazon.com
Engineering economic decisions -- Accounting and financial decision making -- Interest rate and economic equivalence -- Understanding money and its management -- Present - worth analysis -- Annual equivalent-worth analysis -- Rate-of-return analysis -- Cost concepts relevant to decision making -- Depreciation and corporate taxes -- Developing project cash flows -- Inflation and its impact on project cash flows -- Project risk and uncertainty -- Real-options analysis -- replacement decisions -- Capital-budgeting decisions -- Economic analysis in the service sector
Includes index.
Keywords: Engineering economy